Multinational Production and Global Shock Propagation during the Great Recession - Haishi Li (CESifo GmbH, 2025)
Using a new database on global multinational production (MP), I document that world multinational enterprise (MNE) sales declined as sharply as trade during the Great Recession. This collapse was driven by MNEs from a few key headquarters countries, associated with steeper GDP declines in MP-intensive countries. MNEs amplified the trade collapse because their overall sales fell while they maintained higher trade intensity than domestic firms. In a calibrated quantitative model with flexible vertical and horizontal MNE structures, international trade, and input-output linkages, I show that supply shocks contributed more to the trade collapse than demand shocks, as productivity shocks disproportionately affected trade-intensive MNEs. MNE productivity shocks contributed over half of global GDP decline during the Great Recession. MP linkages significantly amplified the impact of headquarters-country domestic productivity shocks on global GDP, MP, and trade.
Keywords: F12; 330; Multinational Production; International Trade; Great Recession; Internationale Produktion; Außenhandel; Multinationales Unternehmen; Weltwirtschaftskrise; Welt